Project Suklay (Start urgent killing of lice afflicting youth) a final community immersion - Araneta, Karla Teresa S.; Bugayong, Andrienne Marrie S. (2009.)
Pediculosis is the infestation of humans by the head lice, Pediculus capitis. Head lice are ectoparasites which inhabit the scalp and hair of humans and causes intense itching to the host. Head lice infestation is a persisitent and growing problem ; a common chronic disease affecting children of school age. Project Suklay is a project proposed by the Team SAINT(Students Acting on he Immediate Needs to Today) to address the problem of Pediculosis in Brgy. Calagtangan, Miag-ao,Iloilo. his project primarily aims to reduce the prevalence of Pediculosis among children ages 4-12 yrs. by at least 80% in this barangay. The purpose ofthe project is to increase the skills and knowledge of parents and children on the proper management of Pediculosis as well as to improve their attitude and practices through series of lectures and forums regarding the disease.
Thesis (Undergraduate, Bachelor of Science in Public Health) College of Arts and sciences, University of the Philippines Visayas, Miag-ao, Iloilo
Keywords: Pediculus capitis (Head lice)